The legality of living trust as an instrument for Muslim estate planning in peninsular Malaysia - Halim, Akmal Hidayah (s.n, 2012)
This instrument has been legally recognised to be applicable to Muslims in Malaysia and is enforceable against the settlor or his estate, irrespective of whether or not possession of the property was given to the beneficiary during the lifetime to the settlor or whether or not the settlor enjoyed the property during his lifetime. This situation is inconsistent with the rule of islamic law on gift (hibah) and succession, especially when the beneficiary is a person who has the legal capacity to own property and who may be one of the legal heirs of the deceased-settlor.